Association Analysis of Polymorphisms in Genes Related to Oxidative Stress in South Indian Type 2 Diabetic Patients with Retinopathy. (2nd January 2016) - Narne, Parimala; Ponnaluri, Kamakshi Chaithri; Siraj, Mohammed; Ishaq, Mohammed
Abstract: Background : Diabetic Retinopathy (DR) is one of the most common microvascular complications of type 2 diabetes mellitus (T2DM) and is polygenic with a multitude of genes contributing to disease susceptibility. The present study aimed at exploring the association between DR and seven polymorphisms in oxidative stress-related genes, i.e. ACE, eNOS, p22phox subunit of NAD(P)H oxidase, PARP-1 and XRCC1 in South Indian T2DM subjects. Materials and methods : The study included 149 T2DM subjects with DR (diagnosed through funduscopic examination) and 162 T2DM patients with no evidence of DR. The selected polymorphisms were genotyped by polymerase chain reaction (PCR) and Taqman allele discrimination assay. Results : There was no significant difference in the genotype and allele distribution of ACE ins/del, eNOS-786T>C, 894G>T, 4a4b and p22phox 242C>T polymorphisms between T2DM groups with and without DR. Contrastingly, there appeared to be a significant association of PARP-1 Val762Ala and XRCC1 Arg399Gln polymorphisms with DR, wherein 762Ala allele seemed to confer significant protection against DR ( p = 0.01; OR = 0.51 [0.3–0.86]), while the presence of 399Gln allele was associated with an enhanced risk for DR ( p = 0.02; OR = 1.52 [1.07–2.15]). Multiple logistic regression analysis revealed a significant and independent association of Val762Ala and Arg399Gln polymorphisms and other putative risk factors with DR in T2DM individuals. Conclusions : The polymorphisms in the DNA repair genes PARP-1 and XRCC1 tended to associate significantly with DR. While Val762Ala polymorphism was associated with reduced susceptibility to DR, the Arg399Gln polymorphism contributed an elevated to risk for DR in South-Indian T2DM individuals.